2014
DOI: 10.1071/wr14033
|View full text |Cite
|
Sign up to set email alerts
|

Is wedge-tailed eagle, Aquila audax, survival and breeding success closely linked to the abundance of European rabbits, Oryctolagus cuniculus?

Abstract: Context Some ecologists argue that nesting success and abundance of wedge-tailed eagles (Aquila audax) are strongly linked to the abundance of introduced wild rabbits (Oryctolagus cuniculus). Consequently, concerns were expressed about eagle population viability when the biological control agent rabbit haemorrhagic disease virus (RHDV) heavily reduced rabbit numbers. However, observations following the spread of rabbit haemorrhagic disease (RHD) in Australia and Spain (where Aquila adalberti is an equivalent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Steele and Baker‐Gabb (2009) could not detect any effect of the introduction of RHD on the abundance of Wedge‐tailed Eagles or any other raptors that normally take rabbits. Olsen et al (2014) found that Wedge‐tailed Eagles exploited the increased abundance of gray kangaroos ( Macropus giganteus ) as the rabbit population fell and there was no sudden decrease in eagle egg clutch size or fledgling survival associated with the spread of RHD. Again, contrary to expectations by some researchers, there was no strong evidence that reduction of rabbit prey seriously compromised native predators.…”
Section: Rabbits and Predatorsmentioning
confidence: 99%
“…Steele and Baker‐Gabb (2009) could not detect any effect of the introduction of RHD on the abundance of Wedge‐tailed Eagles or any other raptors that normally take rabbits. Olsen et al (2014) found that Wedge‐tailed Eagles exploited the increased abundance of gray kangaroos ( Macropus giganteus ) as the rabbit population fell and there was no sudden decrease in eagle egg clutch size or fledgling survival associated with the spread of RHD. Again, contrary to expectations by some researchers, there was no strong evidence that reduction of rabbit prey seriously compromised native predators.…”
Section: Rabbits and Predatorsmentioning
confidence: 99%
“…Wedge-tailed eagles ( Aquila audax ) are the largest bird of prey in Australia and are common in arid regions of the continent. These birds are generalist predators that readily shift their diet in response to the availability of prey (Brooker and Ridpath 1980 ; Leopold and Wolfe 1970 ; Olsen et al 2014 ; Parker et al 2007 ; Silva and Croft 2007 ). In arid Australia, eagles prey heavily on rabbits and reptiles but also prey on larger species such as kangaroos and sheep (Brooker and Ridpath 1980 ; Fuentes and Olsen 2015 ; Sharp et al 2002b ).…”
Section: Introductionmentioning
confidence: 99%
“…After European Rabbit eradication in Australia, several raptor species experienced reduced clutch sizes (Olsen & Marples 1992). However, the impact of such a reduction in non-native species on predators depends on the dependence of the predator population on the non-native prey and the availability of alternative foods (Tubbs 1974; Olsen et al 2014).…”
mentioning
confidence: 99%